2021
DOI: 10.1111/jvim.16166
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac diagnostic test results and outcomes in 44 dogs naturally infected with Trypanosoma cruzi

Abstract: Background: The protozoal parasite Trypanosoma cruzi causes myocarditis in dogs.Objectives: To describe the cardiac diagnostic test results and outcomes of dogs naturally infected with T. cruzi.Animals: Forty-four client-owned dogs.Methods: Medical records were retrospectively reviewed to identify dogs with an indirect fluorescent antibody test result for T. cruzi ≥1 : 80. Data collected included signalment, cardiac diagnostic test results (ECG, echocardiography, cardiac troponin I) and outcome. Outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…The Rassi score incorporates 6 factors associated with increased risk of death in people including New York Heart Association class III or IV, presence of cardiomegaly on thoracic radiography, echocardiographic segmental or global wall motion abnormalities, nonsustained ventricular tachycardia on ambulatory ECG, low QRS voltage, and male sex 25 . In dogs with CCM, right ventricular enlargement as well as ventricular arrhythmias with a high, modified Lown score have been associated with worse outcomes 26,27 . Development of risk assessment scores might be useful in predicting survival including risk for sudden death in dogs with CCM.…”
Section: Discussionmentioning
confidence: 99%
“…The Rassi score incorporates 6 factors associated with increased risk of death in people including New York Heart Association class III or IV, presence of cardiomegaly on thoracic radiography, echocardiographic segmental or global wall motion abnormalities, nonsustained ventricular tachycardia on ambulatory ECG, low QRS voltage, and male sex 25 . In dogs with CCM, right ventricular enlargement as well as ventricular arrhythmias with a high, modified Lown score have been associated with worse outcomes 26,27 . Development of risk assessment scores might be useful in predicting survival including risk for sudden death in dogs with CCM.…”
Section: Discussionmentioning
confidence: 99%
“…For dogs in this study, arrhythmias and cardiac remodeling were consistent with those reported with Chagas cardiomyopathy including the predominate finding of ventricular arrhythmias and combinations of arrhythmias. [26][27][28]30 In humans with Chagas cardiomyopathy, arrhythmias correlated to disease severity and outcome including risk of sudden death. 2 While cardiac arrhythmias can be the primary manifestation of Chagas disease in humans and dogs, Chagas cardiomyopathy is also characterized by myocardial dysfunction and congestive heart failure in the acute stage of the disease, in young dogs < 1 year of age, and in end-stage chronic infections.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,29 In humans and dogs, remodeling of the right ventricle serves as a marker of overall severity of cardiac disease and has been associated with a worse prognosis. 26,30 While research efforts continue to work to identify effective prophylaxis and antiparasitic treatment for T cruzi infection in dogs, management is predominately symptomatic for cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…with the following data recorded: duration of analysis, heart rate (average, maximum, minimum), presence and number of ventricular premature complexes, presence and number of supraventricular premature complexes, presence of supraventricular tachycardia, number of pauses over 3 s, longest pause > 4 s, and presence of second or third degree atrioventricular block. Ventricular arrhythmias were assigned a modified Lown score based on the highest grade observed as follows: 1 = single ventricular premature complexes, 2 = ventricular bigeminy or trigeminy, 3 = accelerated idioventricular rhythm, 4 = ventricular couplets or triplets, and 5 = ventricular tachycardia or R-on-T phenomenon [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%